STUDI POTENSI EKONOMI PEMANFAATAN LIMBAH INDUSTRI TEKSTIL PRINTING SEBAGAI BAHAN BAKAR ALTERNATIF (STUDI KASUS: PT. SEKAR BENGAWAN, KARANGANYAR) - Badrus Zaman; M. Arief Budihardjo (Universitas Diponegoro, 2012)
Abstract PT. Sekar Bengawan in Karanganyar Regency. Central Java is a printing textile industry which produces 1,25 m3 of kerosene waste per day. Based on technical test, the characteristic of the kerosene waste are as follows, 42,772 MJ/kg of calorific value, 0, 08359 mg/m3 of SO2 emision, and 0,13518 mg/m3 of NO2 emision. The kerosene waste can be used as fuel with the ratio of time length, volume of soot, and weight of soot is 1,72 ; 1,6 ; and 3,1 times bigger than kerosene. Based on exposure assesment of SO2 and of NO2, Hazard index value for adult woman is 0,412; adult man is 0,272 ; child 6-12 years is 0,27;. and child 2-6 years is 0.2725. With hazard index less than one, so kerosene waste will not generate health impact. Based on these data, kerosene waste can be reused and resold to the market. The target market segments are households and street vendors. Kerosene waste which is priced Rp ll75/liters will generate Rp.22.643.437,5 per month of profit compared with Rp.50.625.000 per month of cost if it is treated an hazardous waste treatment. Key word : Waste kerosene, Hazard Index, Reuse, Economic potency